Desain Sistem Persediaan Berbasis Microsoft Access Pada UMKM Bengkel Mobil HJ di Kota Palembang - putra, ali santana; Jauhari, Hadi; Maretha, Fetty (Jurnal Pengabdian Manajemen, 2024)
This article shows the difficulty of HJ Car Workshop MSMEs in determining the final inventory balance, for this reason this activity was carried out to help these MSMEs by designing an inventory system with the help of the Microsoft Access application. The method for carrying out activities begins with data collection, namely observing the recording process that occurs, interviews with partners, namely the owner and administration, and documentation of recording inventory of merchandise in MSMEs. Next, design the merchandise inventory system by considering People Resources, Hardware Resources, Software Resources, Data Resources, and Network Resources. The result of the activity is the design of an inventory system for both incoming and outgoing goods inventory, which is expected to be more efficient and more accurate compared to previous manual recording. Furthermore, it is hoped that HJ Car Repair MSMEs can implement an inventory system design to make it easier to record their inventory.